Strategies to Reduce Hospital Mortality in Lower and Middle Income Countries (LMICs) and Resource-Limited Settings 2019
DOI: 10.5772/intechopen.84282
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Hospital Mortality, Morbidity and Health Outcomes

Abstract: Nutrition has a strong positive linear relationship with hospitalisation, recovery and death. Nutritional status serves as an independent predictor of hospital morbidity and mortality. There is an ensuing academic debate concerning the role and magnitude of nutrition in modifying health outcomes and the strategies that are to be employed to ensure nutritional adequacy. Professional, skill, knowledge and experience are important correlates that may modify patient outcomes, but hospitals continue to be under-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Fifty-nine (n=111) per cent of the respondents reported having been diagnosed with at least one noncommunicable condition. Of those who reported having at least one noncommunicable condition (59%, n=111), 51% were of 31-64 years, 31.5% were at least 65 years old (elderly), 16.2% young adults, and 1.8% children (Table 11) A study by Tonstad, Bulter & Fraser (2009) found that North American Adventists who practice a vegetarian lifestyle were heathier than non-vegetarians, which speaks to the direct statistical relationship between dietary intake and life expectancy as well as lower morbidities (see, Fraser, 2009;Rizzo, et al 2011;Lin, Hwang, Liu & Lin, 2012;Wright, 2019). Embedded in this research is the difference between the ideals and the practice Seventh-day Adventists.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-nine (n=111) per cent of the respondents reported having been diagnosed with at least one noncommunicable condition. Of those who reported having at least one noncommunicable condition (59%, n=111), 51% were of 31-64 years, 31.5% were at least 65 years old (elderly), 16.2% young adults, and 1.8% children (Table 11) A study by Tonstad, Bulter & Fraser (2009) found that North American Adventists who practice a vegetarian lifestyle were heathier than non-vegetarians, which speaks to the direct statistical relationship between dietary intake and life expectancy as well as lower morbidities (see, Fraser, 2009;Rizzo, et al 2011;Lin, Hwang, Liu & Lin, 2012;Wright, 2019). Embedded in this research is the difference between the ideals and the practice Seventh-day Adventists.…”
Section: Resultsmentioning
confidence: 99%
“…These physiological changes that are characteristic of spinocerebellar ataxia impact dietary intake and negatively affect lean body mass [3,4]. Importantly weight loss is a predictor of morbidity risk where sepsis and concomitant illnesses were measured outcome criteria [5]. As a consequence of these physical changes and nutritional impact, the healthcare team must be responsive to the special needs of this cohort of individuals to stem possible negative outcomes.…”
Section: Overview Of Spinocerebellar Ataxia and Diet And Nutritionmentioning
confidence: 99%
“…In doing so, it reduces the quality of life of the patient and even increases the risk of death 11,12 . Therefore, evaluating the nutrition status of the patients at the time of hospitalization and forming a treatment plan are as important as the treatment of the disease 13,14 …”
Section: Introductionmentioning
confidence: 99%